Perception des risques de submersion marine et capacité d’adaptation des populations littorales - Bénédicte Rulleau; Hélène Rey-Valette; Hervé Flanquart; Anne-Peggy Hellequin; Catherine Meur-Ferec (VertigO)
This article proposes the results of a survey dealing with coastal submersion risk perception in three communes in Languedoc-Roussillon (France). This survey was conducted in 2009 on both residents and tourists. Responses regarding the mitigation of the erosion risk are shared between soft and hard techniques. Only 15% of residents are in favour of laissez-faire or managed retreat. Indeed, main and especially secondary residents are strongly attached to the territory where they live. On the contrary, tourists and excursionists, who would be less directly affected by these measures, privilege laissez-faire or managed retreat (respectively 25.5% and 48%). These results give information about populations’ capacities to adapt and favourite adaptation policies and provide decisive elements in the definition of public policies.